Analysis of Knowledge and Nurse Competencies Related to Advanced Care for Trauma Patients in the Emergency Room in South Sulawesi - Yustilawati, Eva; Zahrani, Gina; Fitriani, Aidah; Ria, Purnama; Hakim, Suhatman A. (Universitas Pendidikan Indonesia, 2023)
The Emergency Room is a unit that provides initial treatment for trauma patients. Trauma cases contribute to disability and suffering, making it the fourth leading cause of death worldwide. In 2021, the prevalence of trauma-related deaths was approximately 4.4 million people globally, with 8% of cases resulting in death. This phenomenon highlights the importance of health workers, possessing specialized knowledge and competence in emergencies, including triage, primary,and secondary assessment. The purpose of this study is to analyze the relationship between knowledge and nurse competence in providing follow-up care for trauma cases at the ER in South Sulawesi.The research method utilized in this study is quantitative, employing a cross-sectional approach with a total sample of 37 respondents selected through the total sampling technique. The research was conducted at Ibnu Sina Hospital and Bayangkara Hospital in Makassar. Data were collected through questionnaires and competency observation sheets, and subsequently tested using a correlation test.The results of the univariate test indicate that nurses possess good knowledge in various aspects of follow-up care, including triage, primary survey, and secondary survey. Additionally, their competencies in these areas are also well-developed. The correlation test revealed significant relationships between knowledge and triage competence (p-value of 0.01), knowledge and primary survey competencies (p-value of 0.047), as well as knowledge and secondary survey competencies (p-value of 0.04). These findings suggest that a higher level of knowledge among Emergency Room nurses regarding follow-up care corresponds to better competence in managing trauma cases in the emergency room. In this study, it can be concluded that there exists a relationship between nurses' knowledge regarding follow-up care and their competence in three aspects: triage, primary survey, and secondary survey. Based on these findings, it is recommended that nurses can enhance their competencies through training and can apply high-quality cardiopulmonary resuscitation to improve patient safety.